2020
DOI: 10.1371/journal.pone.0237323
|View full text |Cite
|
Sign up to set email alerts
|

Weekend and weekday associations between the residential built environment and physical activity: Findings from the ENABLE London study

Abstract: Background We assessed whether the residential built environment was associated with physical activity (PA) differently on weekdays and weekends, and contributed to socioeconomic differences in PA. Methods Measures of PA and walkability, park proximity and public transport accessibility were derived for baseline participants (n = 1,064) of the Examining Neighbourhood Activities in Built Living Environments in London (ENABLE London) Study. Multilevel-linear-regressions examined associations between weekend and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(85 reference statements)
1
5
0
Order By: Relevance
“…Moreover, youth living in rural farm or urban environments generally have better access to sports facilities compared to rural desert youth. Moreover, these results are consistent with a range of previous studies in children and young people indicating associations between built environmental factors, PA participation and weight status (Rodriguez and Vogt, 2009, Saelens et al, 2012, Sallis et al, 2018, Clary et al, 2020, Arellana et al, 2020. Although the current findings contribute novelty and can be generalisable in other context of environments and cultures, it is important to note that inactivity and obesity prevalence are highly prevalent amongst demographic groups in Al-Ahsa.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, youth living in rural farm or urban environments generally have better access to sports facilities compared to rural desert youth. Moreover, these results are consistent with a range of previous studies in children and young people indicating associations between built environmental factors, PA participation and weight status (Rodriguez and Vogt, 2009, Saelens et al, 2012, Sallis et al, 2018, Clary et al, 2020, Arellana et al, 2020. Although the current findings contribute novelty and can be generalisable in other context of environments and cultures, it is important to note that inactivity and obesity prevalence are highly prevalent amongst demographic groups in Al-Ahsa.…”
Section: Discussionsupporting
confidence: 91%
“…A systematic review conducted by (Larson et al, 2009) found that neighbourhood residents who have access to supermarkets and limited access to convenience stores tend to have healthier diets and lower levels of obesity. Moreover, an increasing number of studies examining the association between PA and built environment has been documented, but most studies were conducted in Western countries, particularly in the USA and UK (Rodriguez and Vogt, 2009, Saelens et al, 2012, Sallis et al, 2018, Clary et al, 2020, Arellana et al, 2020. To the best of researchers' knowledge, no study conducted in Saudi Arabia to determine the effects of the built environment on PA and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Geographic patterns of MVPA on weekdays were similar to the patterns on weekends. However, we observed a higher concentration of individuals in MVPA clusters during weekdays, which may highlight different physical activity interactions of individuals with their built environment depending on the day of the week [49, 50]. The comparison of the GGIR algorithm with the PAMPRO methodology to calculate MVPA showed some similarities but also some differences in their MVPA spatial distribution.…”
Section: Discussionmentioning
confidence: 94%
“…Geographic patterns of MVPA on weekdays were similar to the patterns on weekends. However, we observed a higher concentration of individuals in MVPA clusters during weekdays, which may highlight different physical activity interactions of individuals with their built environment depending on the day of the week [ 54 , 55 ]. The comparison of the GGIR algorithm with the PAMPRO methodology to calculate MVPA showed some similarities but also some differences in their MVPA spatial distribution.…”
Section: Discussionmentioning
confidence: 99%